Origem e transformação das cidades da nova alta paulista - a contribuição da infraestrutura ferroviária - Souza, Andrews de (2020)
This research explores the relationship of railroad and the urban dynamics, the genesis of the implantation and the expansion process are investigated. The study uses empirical analysis of reading and interpretation of documentary and cartographic sources to explore the urbanization process of the region known as Nova Alta Paulista (extreme west of São Paulo), which appeared along the railroad of Companhia Paulista de Estradas de Ferro (CPEF), branch of tronco oeste. To what extent the railway infrastructure acted as a structuring element in the urban development of these cities. Therefore, this research aims to rescue the regional formation of these cities in order to understand their current morphological aspects. Thus, studying their urban development allows us to understand their relationship and how they interfere with the flow of today's society. The study uses morphological analysis to explore the urbanization process of the cities representing the micro regions of Nova Alta Paulista (Adamantina, Dracena and Tupã). The research reinforces the importance of historical rescue to highlight the impact of regional infrastructure on urban development.